Evaluation of additively manufactured ultraperformance polymers to use as thermal protection systems for spacecraft. Issue 37 (19th February 2020) - Kafi, Abdullah; Wu, Hao; Langston, Jon; Atak, Ozen; Kim, Haewon; Kim, Steven; Fahy, William P.; Reber, Roderick; Misasi, John; Bateman, Stuart; Koo, Joseph H.
Abstract: In this study, high‐temperature thermoplastic polymers were three‐dimensional (3D) printed and evaluated for ablation performances for the first time. The purpose of this study is to fabricate, test, and evaluate several ultraperformance thermoplastics, including polyetherimide (PEI), polyether ether ketone (PEEK), and poly(ether ketone ketone) (PEKK) for thermal, flammability, and ablation properties using fused filament fabrication. Among all tested materials, PEKK exhibit the highest char yield while the two PEEKs exhibit the highest decomposition temperature. Although PEI have the lowest onset decomposition temperature, microscale combustion calorimetry results indicate that it has the lowest heat release properties. For the 15 s oxyacetylene test bed (OTB) ablation test, all five materials experienced various amount of intumescent or swelling behavior. Samples after 30 s test experienced greater mass loss among which PEKK and ULTEM 9085 shows the highest char yield. Scanning electron microscopy microstructural analysis of the char and pyrolysis zones reveal highly porous char structures caused by the rapid generation of the volatile decomposition products. To fully exploit the experimental data provided by the OTB, the flowfield generated during aerothermal testing using this heat source was modeled. Computational fluid dynamics analysis using Ansys/Fluent 19.1 code was used to the heat transfer between the ablative surface and the combustion gases generated by the OTB and compared with experimental results. Abstract : Charred surface of three‐dimensional printed poly(ether ketone ketone).